Land use change in Baghdad City and assessment of the Jadriyah and Umm Al- Khanazeer Island Important Bird Area (IBA) from 1984 to 2020 (Baghdad Science Journal, 2022)
Land use change, particularly the expansion of urban areas and associated human activities at the expense of natural and semi-natural areas, is a major ecological issue in urban areas around the world. Climate change being a very strong additional driver for changing the temperature and habitat in the cities. This also applies to Baghdad, Iraq, where urbanisation and climate change exerts a major pressure on the natural habitats of the city, and thus may affect the ability of city planners to adapt to future climate change scenarios. Here we present evidence of substantial growth in urban areas, increases in temperature, and degradation of natural vegetation within Baghdad city by using Remote Sensing techniques and an assessment for the Jadriyah and Umm Al-Khanazeer site (JUKI). These changes were associated with loss of bird species richness within the area, which was previously the only Important Bird Area (IBA) within the city. A standardised scoring system (following Birdlife International global framework) was used to assess Pressure-State-Response:  JUKI site scored 3-5 for pressure (Medium), two for the state (Moderate), and two for the response (Low). Despite the degradation highlighted in Baghdad city, the JUKI site still has 88% intact habitat to support bird trigger species. We conclude that the site urgently needs a detailed management plan to ensure the protection of its habitats and avian fauna, and that the area should be declared as a protected area according to the “IUCN Category IV: Habitat/Species Management Area; to provide a means by which the urban residents may obtain regular contact with nature”, and re-designated JUKI as an IBA site. The study also identifies the most affected areas in the city of Baghdad, which should take the priority of the afforestation efforts and any future restoration campaigns.